#### Answer

$y$ = -3 , $x$ = 2

#### Work Step by Step

$x$ = -1 - $y$
3(-1 - $y$) + 2$y$ = 0
-3 - 3$y$ + 2$y$ = 0
$y$ = -3
$x$ = -1 - (-3)
$x$ = -1 + 3
$x$ = 2

Published by
Cengage Learning

ISBN 10:
1-13311-087-8

ISBN 13:
978-1-13311-087-3

$y$ = -3 , $x$ = 2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.